Challenging Gender Inequality through Qur’anic Reinterpretation: The Hermeneutics of Nasr Hamid Abu Zaid - Maulida Khasanah; Moh. Nor Ichwan; Muhammad Yusuf Pratama (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
Gender discrimination in contemporary Muslim societies is often rooted in literal interpretations of certain Qur’anic verses perceived as gender-biased, particularly those related to polygamy and inheritance. This study aims to analyze and evaluate Nasr Hamid Abu Zaid’s hermeneutical approach in addressing gender issues within Qur’anic interpretation. Employing a qualitative method, the research utilizes a critical-comparative hermeneutic textual analysis by examining Abu Zaid’s major works alongside selected classical and modern exegeses. The findings indicate that Abu Zaid’s hermeneutics successfully trace the historical and cultural roots of gender bias in traditional interpretations. His approach provides an alternative framework for reinterpretation that considers socio-historical contexts, allowing for a more equitable and dynamic understanding of Qur’anic messages. Abu Zaid differentiates between the divine text and its historically constructed interpretations, advocating for a reinterpretation that aligns with evolving social realities and the principles of justice and equality. This study affirms that religious texts are inherently dynamic and open to reinterpretation, especially when read through a contextual and gender-conscious lens. Abu Zaid’s hermeneutics contribute significantly to the development of a progressive methodology in Qur’anic exegesis, offering critical insights for addressing gender justice in modern Muslim contexts. Consequently, this research introduces a renewed perspective in the discourse of gender and Islamic hermeneutics that is both theologically grounded and socially responsive